Comparison of Reverse Sural Artery Fasciocutaneous Flap in Soft Tissue Reconstruction Between above Ankle and Below Ankle Defect - Pandey, S.; Bidary, S. (Kathmandu University Medical Journal, 2022)
Background Fasciocutaneous reverse sural artery flap is a popular option to treat soft tissue defects in the distal leg, ankle, and foot region. Objective To compare the results of sural artery flap reconstruction between the above ankle and below ankle soft tissue defect. Method It was a retrospective study of sural flap reconstruction of varied etiology for the defect grouped as above ankle and below ankle operated over a period of five years. Flap and graft take-up, rate of primary healing, margin necrosis, and complications were the assessed outcome variables. Result There were a total of 37 patients, 17 cases of the above ankle and 20 cases of below ankle sural flap reconstruction analyzed in the study. Road traffic accident was the most common cause and the mean size of the defect was 40.70 cm2. The overall flap take-up rate was 94.6%, partial margin necrosis was in 6 patients, and > 50% flap necrosis was in 2 cases. The rate of primary healing, margin necrosis and mean healing time were 17 (100%) vs 12 (60%), 0 vs 8 cases (6 margin necrosis and 2 cases of > 50% of flap necrosis), and 20.04 days vs 22.50 days respectively in the above ankle and below ankle flap reconstruction groups. These differences were statistically significant. Conclusion Fasciocutaneous reverse sural artery flap is an excellent choice for reconstruction of the defect at the distal leg and around the ankle region with a high success rate. Below ankle flap reconstruction showed a higher rate of margin necrosis, longer healing time, and less rate of primary healing as compared to the above ankle group.